2023
DOI: 10.1038/s41420-023-01521-y
|View full text |Cite
|
Sign up to set email alerts
|

NSUN2 stimulates tumor progression via enhancing TIAM2 mRNA stability in pancreatic cancer

Abstract: NSUN2 is a nuclear RNA methyltransferase which catalyzes 5-methylcytosine (m5C), a posttranscriptional RNA modification. Aberrant m5C modification has been implicated in the development of multiple malignancies. However, its function in pancreatic cancer (PC) needs to be elucidated. Herein, we determined that NSUN2 was overexpressed in PC tissues and related to aggressive clinical features. Silence of NSUN2 by lentivirus weakened the capability of proliferation, migration and invasion of PC cells in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies have shown that RNA m 5 C methylation can be directly recognized by readers (ALYREF or YBX1), affecting RNA processing and subsequent effects [ 30 ]. In our experiments, we found that the protein expression of ALYREF was elevated in the retinal tissues of DB/DB mice, whereas the change in the protein expression of YBX1 was not significant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that RNA m 5 C methylation can be directly recognized by readers (ALYREF or YBX1), affecting RNA processing and subsequent effects [ 30 ]. In our experiments, we found that the protein expression of ALYREF was elevated in the retinal tissues of DB/DB mice, whereas the change in the protein expression of YBX1 was not significant (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 , 13 , 17 , 18 , 19 , 35 ] NSUN2 promotes the progression of multiple cancers via m 5 C modification of LIN28B , FABP5 , p57 Kip2 , PFAS , TIAM2 , and HDGF mRNA in esophageal squamous cell carcinoma, osteosarcoma, gastric cancer, retinoblastoma, pancreatic cancer and bladder cancer, respectively. [ 10 , 18 , 43 , 44 , 45 , 46 ] Correlation analysis further revealed that high levels of NSUN2 were significantly associated with clinical stage, lymph node metastasis, and distant metastasis. To verify these findings, colony formation, transwell invasion, and tumor sphere formation assays demonstrated that NSUN2 knockout significantly suppressed the proliferation, invasion, and cancer stemness of CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, knockdown of YBX1 remarkedly inhibited cell invasion with downregulation of MMPs in vitro [110]. Silencing of YBX1 led to a reduction in T cell lymphoma invasion and metastasis mRNA stability, which mediated EMT migration and invasion in pancreatic cancer cells [132]. Abbreviations: SMURF2: SMAD-specific E3 ubiquitin protein ligase 2; CBX3: chromobox protein homolog 3; TIAM2: T cell lymphoma invasion and metastasis; MMPs: Matrix metalloproteinases; NUF2: cell division cycle-associated 1; PDXK: pyridoxal kinase.…”
Section: Role Of Ybx1 In Activating Invasion and Metastasismentioning
confidence: 90%
“…Moreover, knockdown of YBX1 remarkedly inhibited cell invasion with downregulation of MMPs in vitro[110]. Silencing of YBX1 led to a reduction in T cell lymphoma invasion and metastasis mRNA stability, which mediated EMT migration and invasion in pancreatic cancer cells[132]. Abbreviations:…”
mentioning
confidence: 99%